Constitutive mutations of Agrobacterium tumefaciens transcriptional activator virG - Gregory J. Pazour; Christopher N. Ta; Anath Das (1992)
The virulence (vir) genes of Agrobacterium tumefaciens Ti plasmids are positively regulated by virG in conjunction with virA and plant-derived inducing molecules. A procedure that utilizes both genetic selection and a genetic screen was developed to isolate mutations in virG that led to elevated levels of vir gene expression in the absence of virA and plant phenolic inducers. Mutants were isolated at a frequency of 1 in 10(7) to 10(8). Substitution mutations at two positions in the virG coding region were found to result in the desired phenotype. One mutant had an asparagine-to-aspartic acid substitution at residue 54, and the other contained an isoleucine-to-leucine substitution at residue 106. In both cases, the mutant phenotype required the presence of the active-site aspartic acid residue at position 52. Further analysis showed that no other substitution at residue 54 resulted in a constitutive phenotype. In contrast, several substitutions at residue 106 led to a constitutive phenotype. The possible roles of the residues at positions 54 and 106 in VirG function are discussed.